Staying Home to Give Birth: Reasons of Rural Women in West Java to Choose Home Birth - ., Juariah (KnE Life Sciences, 2019)
The Indonesia Maternal Mortality Rate (MMR) is still high. One of the efforts to decrease the rate, the Indonesian government, make a policy that every woman must give birth in a health care facility assisted by trained health providers. In reality, there are many women who still choose to give birth at home; even they have to pay because the birth at home is not covered by health insurance. The study aimed to determine the reasons why rural women prefer a home birth, seeking information before choosing home birth and factors that supported and inhibited for giving birth at home. A qualitative approach was made. A Total of 29 women from Campakamulya Village, Cianjur District who planned to give birth at home in their current pregnancy and who gave birth at home within the last six months were interviewed. Respondents were chosen by using purposive sampling. Interviews provided data for content analysis. This study showed that there were three main reasons rural women chose home birth. The first was comfort reason, birthing at home surrounded by family, high autonomy dan readily available birthing equipment and supplies. The second was believed to tradition reason. Giving birth at home allowed women to practice their beliefs. The third was a safety reason. Inadequate infrastructure, lack of transportation made the women felt safer to stay at home to give birth. Before choosing the home birth, the women sought information from people who were closed with them. There were factors that supported and inhibited women to choose home birth. Support from the closed people and normal condition of their pregnancy were the supporting factors while cost and attitude of health care providers were the inhibiting factors. Keywords: Reasons, Home birth, Rural Women